Plasma NT-proBNP and pulmonary to systemic blood flow ratio in congenital heart defects with left-to-right shunts - Eko Kristanto Kunta Adjie; Ni Putu Veny Kartika Yantie; Made Gede Dwi Lingga Utama; Eka Gunawijaya; Ketut Ariawati; Ida Bagus Subanada; Anak Agung Ngurah Ketut Putra Widnyana (Indonesian Pediatric Society, 2020)
Background Cardiac left-to-right shunts changes to the pulmonary-to-systemic blood flow ratio (Qp/Qs ratio). This ratio can be used to monitor the hemodynamics of the heart. Left-to right-shunts cause the release of amino terminal proB-ty natriuretic peptide (NT-proBNP) that can be utilized as a specific marker for the presence of heart failure in children with congenital heart defects (CHDs). Early intervention such as defect closure in CHD is important to prevent heart failure. Objective To assess for a correlation between the level of NT pro-BNP and Qp/Qs ratio in CHD patients with left-to-right shunts. Methods This cross-sectional, analytical study was conducted in 32 children who underwent cardiac catheterization at Sanglah General Hospital, Denpasar, Bali, and were recruited by consecutive sampling. NT-proBNP levels were measured by ELISA with a two-step sandwich assay system; Qp/Qs ratio using Fick rules. Statistical analyses included Shapiro-Wilk test, descriptive analysis for subject characteristics, and Pearson’s correlation analysis. A P value of <0.05 was considered to be statistically significant. Age and defect size were analyzed as confounding factors by partial correlation test. Results The correlation value between NT-proBNP and Qp/Qs ratio was r=0.384 (P<0.05), after controlling for age and defect size as cofounding factors. Conclusion There is a weak positive correlation between NT-proBNP levels and pulmonary-to-systemic blood flow ratio in patients with left-to-right shunt, after controlling for age and defect size as confounding factors.